2019
DOI: 10.1007/s11336-019-09679-0
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Comparison of Latent Variable Models: Conditional Versus Marginal Likelihoods

Abstract: Typical Bayesian methods for models with latent variables (or random effects) involve directly sampling the latent variables along with the model parameters. In high-level software code for model definitions (using, e.g., BUGS, JAGS, Stan), the likelihood is therefore specified as conditional on the latent variables. This can lead researchers to perform model comparisons via conditional likelihoods, where the latent variables are considered model parameters. In other settings, however, typical model comparison… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 56 publications
0
74
0
Order By: Relevance
“…In a Bayesian latent variable modeling analysis, the conditional likelihood is relatively easier to obtain than the marginal likelihood because it does not require integration and is readily available in many Bayesian software programs, such as JAGS, OpenBUGS, and Stan. However, in recent studies (e.g., Merkle et al, 2019;Zhang et al, 2019), it is reported that employing the conditional likelihood in model selection can be misleading. Merkle et al (2019) recommended use of marginal likelihood based information criteria in Bayesian latent variable analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a Bayesian latent variable modeling analysis, the conditional likelihood is relatively easier to obtain than the marginal likelihood because it does not require integration and is readily available in many Bayesian software programs, such as JAGS, OpenBUGS, and Stan. However, in recent studies (e.g., Merkle et al, 2019;Zhang et al, 2019), it is reported that employing the conditional likelihood in model selection can be misleading. Merkle et al (2019) recommended use of marginal likelihood based information criteria in Bayesian latent variable analysis.…”
Section: Resultsmentioning
confidence: 99%
“…We computed the three model comparison criteria based on marginal likelihoods as recommended in Merkle et al (2019). The traditional GMM has a closed form of the marginal likelihood:…”
Section: Model Selectionmentioning
confidence: 99%
“…To calculate the likelihood of the model parameters, we follow Merkle et al (2018) and use the marginal likelihood to derive the model selection criteria because we want to infer to a population beyond the specific sample considered. The correlation σ θ 1 θ 2 is the only component of Σ θ 1 2 that needs to be estimated, so we define δ = ( ω , σ θ 1 θ 2 false) T as the vector consisting of all model parameters to be estimated.…”
Section: Modeling Item Positions In An Irt Frameworkmentioning
confidence: 99%
“…which is a weighted version of the marginal likelihood described in Merkle et al (2018) with corresponding log pseudo-likelihood…”
Section: Modeling Item Positions In An Irt Frameworkmentioning
confidence: 99%
“…In recent years, latent variable models have emerged as an important method in various applications. 14 The importance of modeling extra constructs representing other latent variables instead of manifest variables has been recognized by many experts and researchers. 57 In this case, we consider building a hierarchical latent variable model to establish high-level constructs that reflect other latent variables.…”
Section: Introductionmentioning
confidence: 99%